A ratiometric fluorescence sensor based on enzymatically activatable micellization of TPE derivatives for quantitative detection of alkaline phosphatase activity in serum. Issue 45 (20th July 2020) - Lee, Jeongmoo; Kim, Seoyun; Kim, Tae Hoon; Lee, Seoung Ho
Abstract : A novel ratiometric fluorescence assay via enzymatically activatable micellization in aqueous solution was devised for quantitative detection of alkaline phosphatase (ALP) activity. Abstract : A novel ratiometric fluorescence assay via enzymatically activatable micellization in aqueous solution was devised for quantitative detection of alkaline phosphatase (ALP) activity. We demonstrated that the dephosphorylation of the water-soluble, phosphate-functionalized, fluorophore monomer P-TPE-TG, induced by an enzymatic reaction of ALP, leads to micelle formation in aqueous solution because its water-soluble functionality is reduced. The dephosphorylation-induced micellization of P-TPE-TG exhibited a ratiometric sensing response for various ALP concentrations (10–200 mU mL −1 ) and provided a suitable sensing platform for naked eye detection with increased fluorescence quantum yield ( Φ = 3.2%), even compared to a typical TPE-based sensor ( Φ = 1.0%), where ALP can be sensed with a detection limit of 0.034 mU mL −1 . In addition, P-TPE-TG displayed excellent sensing performance at concentrations from 0 to 50 mU mL −1 in diluted human serum (10%), which offers the capability to exploit ratiometric responses for bioactive substances under practical conditions.